Visceral Gout in Coastal and Oceanic Seabirds in Paraná, Southern of Brazil - de Nobrega, Daniela Farias; Domiciano, Isabela Guarnier; Domit, Camila; Rodrigues Loureiro Bracarense, Ana Paula Frederico (Acta Scientiae Veterinariae, 2020)
Background: Owing to the abundance, wide distribution, long life cycles and higher positions in the throfic levels, seabirds are considered sentinels of hazards and negative anthropogenic impacts to marine ecosystems. Gout is a a common disease affecting birds, but also occurs in other taxa, including mammals and reptiles. The aim of this study was to elucidate the occurrence and pathological findings of gout cases in different species of seabirds, including biological and ecological factors that may contribute to disease. Cases: The urate crystals were observed in ten seabirds stranded, classified in eight species: four oceanic species - two Puffinus puffinus, one Macronectis giganteus, one Thalassarche melanophris, one Calonectris sp. and four coastal species - one Fregata magnifiscens, two Sula leucogaster, one Phalacrocorax brasilianus and one Rynchops niger. A total of seven animals were stranded alive and three were found dead; four animals were male and six were female; six were juveniles and four were mature. The nutritional condition was cachectic in four animals, poor in five and fair in one. The main clinical sign in alive animals was dehydration (7/7; 100%). The treatment consisted of standard support including fluid therapy and temperature stabilization; in addition, vitamins, amino acids, minerals and antibiotics (sulfonamide or enrofloxacin) were given, but the animals died between 1 and 13 days after rehabilitation entrance. Gout was associated with cachectic condition and autumn stranding (in comparison with summer stranding). The main macroscopic findings were observed in the kidneys, which were whitish and enlarged and all had microscopic evidence of multifocal, mild to marked renal crystal urate deposition. In two cases, urates deposition were observed in multiple organs, including liver, spleen, lung, epicardium and kidney in two cases, indicating severe visceral gout.The gout was considered the ultimate cause of death in three cases, and in the remaining cases, the main lesion associated with death was trauma (n = 2), infectious enteritis (n = 2), systemic infection (n = 1), myocardial necrosis (n = 1) and cachexia syndrome. The contributing factors for urate deposition were metabolic imbalances, chronic dehydration and overdoses of protein supplements. Discussion:The ten cases described above constitute a rare report of visceral gout in free-living and in rehabilitation seabirds and contributes towards understanding the prevalence and pathogeny of gout in stranded oceanic and coastal animals off southern Brazil. Similar prevalence of gout was observed among free-ranging birds of other reports,but it was considered lower when compared to 21.5% and 23.3% affected captive/broilers. The difference observed may be influenced by the population analysed, but also by the gout pathogeny and environmental conditions. Among the possible causes of gout, dehydration was observed in all gout-affetected animals stranded alive, a change usually observed in debilitated/stranded animals that probably has contributed to the disease. Additionally, the poor/cachectic condition noticed in the majority of seabirds indicates a nutritional disorder, also a cause promoting visceral gout. In the present study, accumulation of urate crystals was predominantly limited to the kidneys and associated with inflammatory infiltrate, suggesting a chronic process. The results of this study support the hypothesis that visceral gout is a complex consequence of multiple factors affecting both free-living and rehabilitated seabirds. Therefore, further investigation of the other possible causes, frequency and consequences for coastal and oceanic species is indispensable.